CLINICAL PROFILE OF PERIPHERAL NEUROPATHY IN GERIATRIC POPULATION - SHARMA, GIRISH KUMAR; JAIN, ANURAG; SENGAR, PUSHPENDRA SINGH; DANDOTIYA, DILEEP (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study was to describe the clinical profile of peripheral neuropathy (PN) in the geriatric population. Methods: This prospective observational study was done among patients >65 years, found to have PN by Neuropathy Symptom Score, who were undergone history and clinical examination at the Department of Medicine and Gandhi Medical College and associated Hamidia Hospital Bhopal. Nerve conduction study was done in all subjects to observe the pattern and type of various peripheral neuropathies. Special investigations such as Serum Vitamin B-12, toxin screening of lead and arsenic, viral serology using the ELISA method, serum and urine electrophoresis, rheumatoid factor, antinuclear antibodies (ANA), and antinuclear cytoplasmic antibodies (c-ANCA and p-ANCA), and CSF examination were done as and when needed. Results: Most of the patients were in the 60–65 years [93 (46.5%)] of age followed by 66–70 years [54 (27%)]. Most common clinical feature was Tingling [120 (60%)] followed by Tingling and Numbness [36 (18%)]. In most of the subjects, deep tendon reflexes were normal [132 (66%)] whereas in 42 (21%) subjects deep tendon reflexes were impaired and in 26 (13%) subjects deep tendon reflexes were absent. Most of the patients had sensory motor axonal demyelinating neuropathy [8 (4%)]. Conclusion: PN is a heterogeneous disease with diverse pathology. Recognition of the clinical homolog of these pathological processes is the first step in achieving the appropriate form of intervention. Treatment should be individualized such that the particular manifestation and underlying pathogenesis of each patient’s unique clinical presentation are considered.